Formy pomocy publicznej dla małych i średnich przedsiębiorstw w Polsce - Czaja, Stanisław; Becla, Agnieszka (Forms of Public Assistance for Small and Medium-sized Enterprises in Poland, 2006)
In the article the authors present forms of public assistance which are used in Poland, especially financial, consultations, legal and social. The authors also take into account EC solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 9-23